RECQL5 is an important determinant for camptothecin tolerance in human colorectal cancer cells. Issue 5 (5th August 2011) - Wang, Xiaoqi; Lu, Xincheng; Zhou, Guangjin; Lou, Hua; Luo, Guangbin
Abstract : CPTs (camptothecins) are an important class of effective anticancer agents that target type I topoisomerase in humans. Irinotecan and topotecan are currently used to treat various types of cancers and many CPT derivatives are being developed. However, these drugs are only effective in a small percentage of each type of cancer and the molecular underpinning for this individualized response to the drug has remained elusive. Thus, identification of the main determinants for cell survival in response to this unique class of drug should help to improve their clinical applications. In the present study, we examined whether RECQL5 constitutes an important determinant of CPT resistance in colon cancer cells. Specifically, RECQL5-deficient derivatives of both DDL1 and HCT116 cells, two colorectal cancer cell lines were generated by adenovirus-based somatic gene-targeting experiments and the CPT sensitivity between the RECQL5-proficient parental lines and their corresponding RECQL5-deficient derivatives were examined. We found that deletion of RECQL5 from DDL1 and HCT116 cells both resulted in a significant enhancement in CPT sensitivity under in vitro culture conditions. More importantly, xenograft tumours derived from RECQL5-deficient HCT116 cells, but not those from the parental line, could be cured by a CPT-based therapy in nude mice. Thus, the present study has identified RECQL5 as a major determinant for CPT resistance in colorectal cancer cells and a potential candidate as a biomarker for irinotecan-based treatment for colon cancer.